Outdoor Air Pollution and Gestational Diabetes Mellitus: A Systematic Review and Meta-Analysis - Mohamed H. ELSHAHIDI (Tehran University of Medical Sciences, 2019)
Background: During the past 20 years, the prevalence of gestational diabetes mellitus (GDM) has increased by ∼10%-100% in several race/ethnicity groups. There is an association between ambient air pollution (AAP) and GDM. This study aimed to summarize the evidence about the association between AAP and GDM. Methods: PubMed, Embase, Scopus, Web of Science and Cochrane Library were searched from inception till Oct 2017. Studies about the association between ambient air pollutants levels and GDM were included. Pooled effect estimates and their 95% confidence interval (CI) were calculated using R. Results: Eight studies met the inclusion criteria. The odds of developing GDM upon exposure to CO (per 1 ppm), NO (per 1 ppb), NO2 (per 10 µg/m3), NOx (per 1 ppb), O3 (per 10 ppb), SO2 (per 10 ppb), PM10 (per 10 µg/m3) and PM2.5 (per 10 µg/m3) were 1.47 (95% CI 0.88-2.06), 1.04 (95% CI 1.03-1.06), 1 (95% CI 0.93-1.08), 1.02 (95% CI 1-1.04), 1.05 (95% CI 0.94-1.16), 1.39 (95% CI 1.04-1.73), 0.97 (95% CI 0.94-0.99) and 1.12 (95% CI 0.93-1.31), respectively. Conclusion: The current literature showed evidence for an association between AAP and GDM. However, further well-designed studies are needed.